Telemedicine. “Childish” diseases or serious problems - V. A. Klochkov (Кардиоваскулярная терапия и профилактика)
For more than a century, attempts to use modern technologies for communication between doctors and patients who are far from medical facilities have continued. At first, this was actualized mainly for the diagnosis and treatment of emergency conditions and was very limited. Recent exponential progress of communication technologies and Internet in most remote places allow both providing quality consultation care and developing disease prevention programs, in particular screening. But, unfortunately, in traditional medical organization, these opportunities cannot be fully actualized. The search for optimal communication forms between a doctor and a patient is ongoing. There remain many unsolved problems of the interaction between state, insurance and private medicine. Nevertheless, the accumulated experience suggests that this very promising branch of medicine will be developed.